2021
DOI: 10.3390/en14206521
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Wind and Solar Photovoltaic Generation with Energy Storage Systems: A Systematic Literature Review and Contributions to Technical and Economic Regulations

Abstract: The operation of electrical systems is becoming more difficult due to the intermittent and seasonal characteristics of wind and solar energy. Such operational challenges can be minimized by the incorporation of energy storage systems, which play an important role in improving the stability and reliability of the grid. The economic viability of hybrid power plants with energy storage systems can be improved if regulations enable the remuneration of the various ancillary services that they can provide. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Wealthier developed nations encounter fewer economic challenges than their less affluent counterparts. In 2021, de Doile et al explored economic feasibility and regulatory issues in hybrid wind and solar PV energy generation [9]. Their findings underscored a lack of attention to hybrid studies, particularly in regulatory and legal aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Wealthier developed nations encounter fewer economic challenges than their less affluent counterparts. In 2021, de Doile et al explored economic feasibility and regulatory issues in hybrid wind and solar PV energy generation [9]. Their findings underscored a lack of attention to hybrid studies, particularly in regulatory and legal aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The economic challenges will be less in richer developed countries compared with poorer developing nations. de Doile et al, [4] examined the economic feasibility and regulatory issues of hybrid wind and solar PV energy generation with energy storage systems. Their results indicated that most scientific studies focused on only one of the RE technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hybridization between some of the RE sources forms a complementarity of energy production and an alternative to conventional generators generally used to produce electricity. An HES design is an important step because of its relationship to completion costs and reliability [3]. Therefore, it is necessary to provide new solutions and focus in particular on meeting consumer demands for energy while ensuring the minimum cost [4].…”
Section: Introductionmentioning
confidence: 99%